The Third Sector as a Renewable Resource for Europe Concepts, Impacts, Challenges and Opportunities - Enjolras, Bernard; Salamon, Lester M.; Sivesind, Karl Henrik; Zimmer, Annette (Springer International Publishing : Imprint: Palgrave Macmillan, 2018)
This book provides a critical account of the third sector and its future in Europe. It offers an original conceptualization of the third sector in its European manifestations alongside an overview of its major contours, including its structure, sources of support, and recent trends. It also assesses the impact of this sector in Europe which considers its contributions to European economic development, citizen well-being and human development. The Third Sector As A Renewable Resource for Europe presents the findings of the Third Sector Impact (TSI) project funded by the European Union's Seventh Framework Program (FP7). It recognises that in a time of social and economic distress, as well as enormous pressures on governmental budgets, the third sector and volunteering represent a unique 'renewable resource' for social and economic problem-solving and civic engagement in Europe.